Input parameters in a one-dimensional neuronal model with reversal potentials - Lánská, V; Lánský, P (Bio Systems, 1998)
An equation for a stochastic neuronal model describing the initiation of action potentials is studied for the case in which the depolarization of the membrane potential is restricted by the reversal potentials. It is assumed that the values of the membrane potential can be continuously recorded between consecutive spikes. Under this assumption, the estimators of the model parameters are derived and the methods for testing the model are proposed. The objective of the methods presented in this contribution is to provide neuroscientists with quantitative means in order to estimate parameters of stochastic neuronal models.
Keywords: modely neurologické; Bayesova věta; Neurons; membránové potenciály; Bayes Theorem; neurony; Membrane Potentials; Models, Neurological